2011
DOI: 10.1016/j.jclinepi.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Variability in measuring (instrumental) activities of daily living functioning and functional decline in hospitalized older medical patients: a systematic review

Abstract: This review shows there is a large variability in measuring (I)ADL functioning of older hospitalized patients and a large range of clinical definitions of functional decline. These conceptual and clinimetric barriers hamper the interpretation and comparison of functional outcome data of epidemiological and clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 45 publications
4
78
0
8
Order By: Relevance
“…It has been demonstrated that several studies used the Katz Index to assess ADL directly by patients or by proxies (informants) (25,27) . The reliability of the scale to assess ADL was synthetized in a review published in 2008 (22) , and the cut-off points for the Katz Index to be considered as indicative of functional decline (27) were demonstrated in www.ee.usp.br/reeusp…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that several studies used the Katz Index to assess ADL directly by patients or by proxies (informants) (25,27) . The reliability of the scale to assess ADL was synthetized in a review published in 2008 (22) , and the cut-off points for the Katz Index to be considered as indicative of functional decline (27) were demonstrated in www.ee.usp.br/reeusp…”
Section: Discussionmentioning
confidence: 99%
“…The range of the sum score was 0-8, and the higher the score the greater the abilities [14,15]. The sum score was then dichotomized with a sum score of 8 indicating complete independency and a sum score <8 indicating disability in one or more of the items [23]. The examination protocol included medical history and information from a family carer, testing of cognitive function (a comprehensive battery), physical examination and a psychiatric evaluation with a primary emphasis on depression.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria were (1) hospital length of stay (LOS) of 2 days or less (n = 108), (b) healthcare-associated pneumonia [either from a residential facility or recent hospitalization in the last 14 days) (n = 92), (c) data missing during matching process (n = 77), or (d) deceased in hospital (n = 31). Functional decline was assessed using the Katz Activities of Daily Living (ADL) Index which is the most common measurement of activities of daily living functioning in hospitalized older medical patients [18]. A score of 0 represents total dependence and 6 represents total independence.…”
Section: Study Subjectsmentioning
confidence: 99%